Acute in Vitro Exposure of Potassium Dichromate on Oxidative Stress, Cell Density, and Cell Viability of Osteochilus Vittatus - Wijayanti Gratiana E.; Mentari Diani; Habibah Aulidya N. (E3S Web of Conferences)
The harmful effect of K2Cr2O7 has been reported in animals and humans but the mechanism in exerting such an effect is unclear. An experimental study applying a completely randomized design was conducted to evaluate the impact of in vitro exposure to K2Cr2O7 on MDA level, cell density, and cell viability in Osteochilus. vittatus testis. The testis fragments were cultured in DMEM supplemented with 10% FBS and 5% pen-strep for 24 hours and 72 hours at 29°C; 5 concentrations of K2Cr2O7: 0µg.mL-1, 0.125 µg.mL-1, 0,250 µg.mL-1, and 0.50µg.mL-1 were tested. The result showed that the exposure of 0.500 µg.mL-1 K2Cr2O7 for 24 hours did not significantly affect the MDA level (p>0.05), but it significantly reduced cell density (p<0.05) and cell viability (p<0.01). Exposure to 0.500 µg.mL-1 K2Cr2O7 for 72 hours significantly increased the DMA level (p<0.05), cell density (p<0.05), and cell viability (0.01). These results indicated that K2Cr2O7 induces oxidative stress, cell proliferation, and cell survival of Osteochilus vittatus testis.